Analysis of Ecolexicons Tuo (Tuak) in Nias Language - Oktober Tafonao; Mirsa Umiyati; I Nyoman Muliana (CV Wahana Publikasi, 2025)
This study examines the ecolexicon of tuo (palm wine) in the Nias language as a reflection of the close relationship between language, environment, and culture in Nias Island, Indonesia. This stud employs qualitative approach to analyze the data. All data were collected in Nias Regency and Gunungsitoli City through observations and interviews with sap tappers and tuo consumers, and other documents such as dictionaries, books, article related study were used as supporting data. The analysis applies the grammatical framework of Bundasgaard (2000) (2000) to classify tuo lexical items into grammatical categories and to interpret their cultural and ecological meanings. The findings reveal 61 tuo lexical items in the Nias language. These include 19 lexical items for types of tuo, 26 lexical items referring to its natural sources (particularly coconut and aren palm), and 39 lexical items related to tools and the management of tuo. Grammatically, the ecolexicon consists of seven nouns, nineteen verbs, and eight adjectives that describe the qualities, processes, and functions of tuo in daily life. The study also shows that tuo lexical items are embedded in Nias proverbs and song lyrics, which encode moral teachings, social norms, and communal values such as self-control, solidarity, prudence, and respect for others. Overall, the tuo ecolexicon functions not only as a linguistic resource but also as a carrier of cultural identity and ecological knowledge. The study underscores the urgency of documenting and preserving this ecolexicon in the face of modernization and the declining use of traditional vocabulary among younger generations.